The right to information - Present status and issues: A banker's perspective - Lakshminarayanan, P. (2009)
The present status of the RTI Act is largely on paper. Many among the bureaucrats to not understand the importance of this Act. They have an apprehension that this Act shall dilute their power, which was used for self-improvement. Many state governments have not appointed/nominated officers as required under the Act for providing the information that is sought by the citizens. The best way is to address these limitations by educating both authorities and the general public for efficacious results and make our democracy really meaningful. - Reproduced.
Keywords: Right to information